Aging affects spatial reconstruction more than spatial pattern separation performance even after extended practice. Issue 6 (31st March 2017) - Clark, Rachel; Tahan, Asli C.; Watson, Patrick D.; Severson, Joan; Cohen, Neal J.; Voss, Michelle
Abstract: Although the hippocampus experiences age‐related anatomical and functional deterioration, the effects of aging vary across hippocampal‐dependent cognitive processes. In particular, whether or not the hippocampus is known to be required for a spatial memory process is not an accurate predictor on its own of whether aging will affect performance. Therefore, the primary objective of this study was to compare the effects of healthy aging on a test of spatial pattern separation and a test of spatial relational processing, which are two aspects of spatial memory that uniquely emphasize the use of multiple hippocampal‐dependent processes. Spatial pattern separation supports spatial memory by preserving unique representations for distinct locations. Spatial relational processing forms relational representations of objects to locations or between objects and other objects in space. To test our primary objective, 30 young (18–30 years; 21F) and 30 older participants (60–80 years; 21F) all completed a spatial pattern separation task and a task designed to require spatial relational processing through spatial reconstruction. To ensure aging effects were not due to inadequate time to develop optimal strategies or become comfortable with the testing devices, a subset of participants had extended practice across three sessions on each task. Results showed that older adults performed more poorly than young on the spatial reconstruction task that emphasized the use of spatial relational processing, and that age effects persisted even after controlling for pattern separation performance. Further, older adults performed more poorly on spatial reconstruction than young adults even after three testing sessions each separated by 7–10 days, suggesting effects of aging are resistant to extended practice and likely reflect genuine decline in hippocampal memory abilities.